1997
DOI: 10.1111/j.1460-2695.1997.tb01515.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Mechanics Applications to Drilling and Blasting

Abstract: This paper gives a brief review of research in rock fracture mechanics as conducted at the Fracture and Photo-Mechanics Laboratory (FPML) at Vienna University of Technology. The mechanisms pertaining to percussion drilling and blasting are investigated, with specific reference to the application of fracture mechanics. In order to gain an improved understanding of the mechanisms controlling rock fragmentation, a multidisciplinary approach is followed which includes laboratory experiments conducted in plexiglass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 11 publications
(7 reference statements)
1
21
0
Order By: Relevance
“…Therefore, it was selected to make the DCSC specimens. Furthermore, the property of PMMA is similar to rock, which has been confirmed by a number of researchers …”
Section: Specimen and Testing Systemsupporting
confidence: 62%
See 1 more Smart Citation
“…Therefore, it was selected to make the DCSC specimens. Furthermore, the property of PMMA is similar to rock, which has been confirmed by a number of researchers …”
Section: Specimen and Testing Systemsupporting
confidence: 62%
“…Furthermore, the property of PMMA is similar to rock, which has been confirmed by a number of researchers. [42][43][44] The DCSC specimen in Figure 1 is 325 mm in height, 200 mm in width, and 15 mm in thickness. The semicircular diameter is 75 mm, and the two crack lengths are the same 25 mm.…”
Section: Dcsc Specimenmentioning
confidence: 99%
“…Fractographic examination showed that, in addition to glass powder and a network of small cracks (Rossmanith et al 1997), some large 'chips' were formed. These are large cracks, which originated at some depth and propagated until reaching the surface of the sample.…”
Section: Fractographic Examinationmentioning
confidence: 99%
“…Authors such as Rossmanith et al (1997), Rathore and Bhandari (2007) and Katsabanis et al (2008) have demonstrated that fracturing can be partially controlled through the application of suitable blast design parameters such as type of explosive, energy distribution and timing.…”
Section: Introductionmentioning
confidence: 98%